Кот в сапогах: сказки / художник Игорь Приходкин - Приходкин И. Н. (Пять сказок, 2012)
Экземпляры: ф.10 (20250303) / Инвентарный номер: 69925 / Цена: 50.00 / Авт.знак: К 73 / ГРНТИ: 17.82.93 / ББК: 84(0)